2014
DOI: 10.1590/s0104-92242014000100004
|View full text |Cite
|
Sign up to set email alerts
|

Aperfeiçoamento da técnica de Soldagem Pontual por Fricção (FSpW) para união de poliamida 6 e laminado de poliamida 66 com fibra de carbono

Abstract: Resumo A Soldagem Pontual por Fricção ('Friction Spot Welding -FSpW') é uma técnica inovadora que foi desenvolvida e patenteada em 2005 pelo centro de pesquisa alemão Helmholtz Zentrum Geesthacht (HZG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…The feasibility of the joining of unreinforced polymers by RFSSW was demonstrated by Oliveira et al [66] in 2010, who successfully welded PMMA plates. The dissimilar joining of unreinforced polymers and FRTP composites by RFSSW was reported in 2014 by Gonçalves et al [67,68]. One year later, by successfully joining CF reinforced PA66 laminate plates, Gonçalves et al [69] demonstrated the joining of FRTP composites by RFSSW.…”
Section: Introductionmentioning
confidence: 94%
“…The feasibility of the joining of unreinforced polymers by RFSSW was demonstrated by Oliveira et al [66] in 2010, who successfully welded PMMA plates. The dissimilar joining of unreinforced polymers and FRTP composites by RFSSW was reported in 2014 by Gonçalves et al [67,68]. One year later, by successfully joining CF reinforced PA66 laminate plates, Gonçalves et al [69] demonstrated the joining of FRTP composites by RFSSW.…”
Section: Introductionmentioning
confidence: 94%
“…Campanelli et al [9] reportaram em seu estudo a otimização dos parâmetros de processo considerando a resistência ao cisalhamento de chapas da liga de magnésio AZ31 com 2 mm de espessura. No campo de união de materiais poliméricos, Gonçalves et al [10] estudaram a otimização dos parâmetros de processo envolvidos na soldagem a ponto por fricção de chapa de poliamida 6 e laminado de poliamida 66 com fibra de carbono. No entanto, não é do nosso conhecimento a publicação de nenhum trabalho anterior relacionado com a otimização de parâmetros de processo para a soldagem a ponto por fricção de chapas finas de ligas de alumínio para aplicação aeronáutica até o presente momento.…”
Section: /401unclassified
“…[9] Mechanical joining includes drilling holes and screwing bolts or rivets, resulting in stress concentration and weight increment. [11] Welding techniques, such as friction stir welding [12][13][14][15] friction spot welding [16][17][18] laser welding, [19] induction spot welding, [20] are alternatives owing to short welding time, high joint quality, and low energy consumption. Despite excellent application potential, sparked with its nontoxicity and outstanding mechanical properties, the low glass transition temperature (T g ) thermoplastic CF/epoxy remains an urgent issue in welding due to its sensitivity to welding heat.…”
Section: Introductionmentioning
confidence: 99%